ANALISIS PENDAPATAN USAHA POLE AND LINE DI PELABUHAN PERIKANAN SAMUDERA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Mimiatin Mimiatin; La Anadi; Akhmad Mansyur (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
The aim of the study were to determine the income of pole and line fishing business based in the Ocean Fishing Port of Kendari and to determine production factors which affect the pole and line fishing business. Data collection was gathered by directly interviewing respondents using a questionnaire. The data was analyzed using a multiple linear regression. The result of study showed that in the whole of parameters the response of operational cost was Rp11.37, while the response of catch production, duration of fishing trip, fishing vessel size, number of crews were 14,809 (tons), 15.82 (days), and 7.81 (people) (p < 0,05). The number of baits was not significantly affect incomegained.